Endoscopic Submucosal Dissection for Recurrent or Residual Superficial Esophageal Cancer after Chemoradiotherapy: Two Cases - Changhyeok Hwang; Young Hoon Youn; Sung-eun Choi; Young Hak Jung; Hae Yeul Park; Jae Jun Park; Jie Hyun Kim; Hyojin Park (Korean Society of Gastrointestinal Endoscopy, 2015)
We report two cases of endoscopic submucosal dissection (ESD) for recurrent or residual esophageal squamous cell carcinoma (ESCC) lesions after chemoradiotherapy for advanced esophageal cancer. Case 1 involved a 64-year-old man who had previously undergone chemoradiotherapy for advanced ESCC and achieved a complete response (CR) for 22 months, until metachronous recurrent superficial ESCC was detected on follow-up esophagogastroduodenoscopy (EGD). We performed ESD and found no evidence of recurrence for 24 months. Case 2 involved a 59-year-old man who had previously undergone chemoradiotherapy for advanced ESCC. He responded favorably to treatment, and most of the tumor had disappeared on follow-up EGD 4 months later. However, there were two residual superficial esophageal lugol-voiding lesions. We performed ESD, and he had a CR for 32 months thereafter. ESD can be considered a viable treatment option for recurrent or residual superficial ESCC after chemoradiotherapy for advanced esophageal cancer.